EVALUASI KINERJA JARINGAN UTAMA DAERAH IRIGASI JEURAM KABUPATEN NAGAN RAYA - Irwansyah Irwansyah; Azmeri Azmeri; Syamsidik Syamsidik (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Irrigation infrastructure does not last long without being supported by continuous maintenance activities as the age of water building grows in irrigation networks. To maintain a sustainable irrigation system an irrigation management system is needed starting from the main building, the primary network to the secondary network. Irrigation Performance is an indicator in order to describe an irrigation system management, performance appraisal according to Minister of Public Works Regulation Number 12/PRT/M/2015 concerning Exploitation and Maintenance of Irrigation Networks is carried out on 6 (six) parameters, namely : Physical Infrastructure, Planting Productivity, Facilities Support, Personnel Organization, Documentation and Water User Farmers Association. The objective of this study was to conduct a performance assessment of D.I Jeuram through observing the condition of irrigation networks and analyzing the irrigation network condition data from the implementing agency D.I Jeuram and information from the P3A as a reference for the performance of D.I Jeuram. The results of this study show that the performance of the Jeuram Irrigation Area in terms of physical and non-physical aspects has a performance index of 69.36%, so that the performance of the Jeuram Irrigation Area falls into the less performance category and needs attention, so efforts to improve performance in Irrigation Areas are suggested. Jeuram, namely the aspect of physical infrastructure consists of routine maintenance activities from the main building to the final secondary canal (B.Jr.30), periodic maintenance includes replacement of the operating board and measuring ruler on the weir, replacement of missing door parts in weir drains, bag draining periodic mud, replacement of 16 door units at Jeuram Kanan and 6 door units at Jeuram Kiri, heavy rehabilitation in buildings tapping B.Jr.9, B.Jr.13, BU.1 and BU.2, and constructing drain inlets in sections carrier channel that functions as a waster. Efforts to improve the performance of aspects of non-physical infrastructure consist of providing adequate facilities for offices, housing and OM implementation warehouses, providing complete irrigation Area data at branch offices and conducting routine meetings related to OM implementation and cropping patterns. With this, the value of the performance of the irrigation system is obtained with a reliable, and which will later become a reference for the management of irrigation networks as a whole.